MAICC model: development of complex thinking through citizen science project evaluation - Olivo-Montaño, Pamela Geraldine; Sanabria-Z, Jorge; Molina-Espinosa, José Martín; Quintero-Gámez, Lorena; Velarde-Camaqui, Davis; Sánchez-Salgado, Lisset Abril; Gonzalez-Mendoza, Miguel; Breda, Adriana; Morales-Maure, Luisa; Alvarez-Icaza, Inés (Frontiers in Education, 2024)
Mainstreaming Open Science within Education 5.0 is becoming central to addressing student competency gaps as traditional education systems struggle to keep up with technological advances. However, the slow adoption of this transformative approach in formal education systems hinders the full realization of student potential, requiring innovative strategies for its practical integration. This study proposes the MAICC Model, a practical and effective tool to foster complex thinking among higher education students by evaluating citizen science projects. The structure of the model included the pairing of Inquiry-Based Learning and Service Learning as pedagogical approaches that support the building of critical and reflective skills among students, allowing for deeper learning applied to real situations. To obtain an evaluative approach to the model, qualitative and quantitative analysis was carried out to assess student participation and the development of key competencies. The findings of the study were (a) the MAICC model promotes complex thinking in higher education students (b) the evaluation of citizen science projects improves students' critical thinking, and (c) the MAICC model is distinctive for its emphasis on citizen science and educational technology. The discussion highlights the significant contribution of citizen science in education, suggesting that future research could explore its implementation in a broader range of disciplines and settings to better understand its impact and potential in 21st-century competency formation.